The Effect of Speed and Agility Training Variations on Dribbling Skills in Soccer Games for Extracurricular Students at SMA Negeri 1 Berau - Rian Bayu Indrawan; Heryanto Nur Muhammad (Jurnal Indonesia Sosial Sains, 2025)
Football requires more player skills compared to other sports, where players must perform well, handle pressure during the game, have sufficient stamina, and have strong resilience. The key aspects of this sort include basic techniques consisting of ball dribbling skills, passing, heading, throwing, and so on. Dribbling is the most important skill among many basic skills because it is the most frequently used technique during a match. Dribbling involves controlling the ball while moving, and this technique helps create space for shooting. The purpose of this study is to determine the effect of speed and agility training on dribbling skills among extracurricular student at SMA Negeri 1 Berau. This research method is a quantitative Quasi-Experimental design. Data were collected using a nonequivalent pretest-posttest group design technique based on Bobby Charlton’s football dribbling test. The first stage of the design is to establish two experimental groups. The second stage is conducting an identical pretest for related groups. Then, both experimental groups are given two treatments, namely speed training variations and agility training variations. After that, both experimental groups are given the same posttest. The research result showed that the t-value (8.323) was greater than the t-table (2.201) with a determination coefficient of 14,9%. Thus, speed and agility training variations affect dribbling skills in football among extracurricular students at SMA Negeri 1 Berau.